(untitled) (Journal of Nepalese Business Studies, 2023)
The tourism sector of Nepal has seen a sharp rise in the number of tourist arrivals in the last one decade; however, its realised economic benefit has not grown at the same pace. This paper, therefore, has delved into this concern using the Keynesian multiplier and MGM2 approach to assess the economic impact of tourism in Nepal. The analysis shows that the fall in both per capita tourist spending and tourism multiplier has jointly cancelled out the monetary benefits originating from the increased number of tourist arrivals. Moreover, the proportion of budget travellers is increasing in the visitors to Nepal, and the demand of increased tourists is catered by imported goods and services. This occurrence in the tourism sector of Nepal has constrained its forward linkages with other sectors of the economy. Therefore, the author recommends that the policymakers should prioritise tourism targets in dollar values and develop differentiated campaigns to attract the high and low-end tourists separately in different months of the year. They should also incentivise and prioritise local productions to strengthen the economic ties between tourism and other sectors of the economy.